Large Area Artificial Spin Ice and Anti‐Spin Ice Ni80Fe20 Structures: Static and Dynamic Behavior. (29th January 2016) - Zhou, Xue; Chua, Geng‐Li; Singh, Navab; Adeyeye, Adekunle O.
Abstract : Artificial spin ice has been the subject of extensive investigation in the last few years due to advances in nanotechnology and characterization techniques. So far, most of the studies have been limited to local probe of small area magnetic elements due to limitations with lithographic techniques used. In this study, large area spin ice and anti‐spin ice Ni80 Fe20 structures with three lattice configurations have been fabricated using deep ultraviolet lithography at 193 nm exposure wavelength. The static and dynamic properties are systematically characterized using vibrating sample magnetometer, magnetic force microscopy, and broadband ferromagnetic resonance spectroscopy. Intriguing static and dynamic behaviors are observed due to the geometrical arrangement of the nanomagnets in the lattice. When the nanomagnets are saturated at high field, multiple resonance peaks whose frequencies are strongly dependent on the orientation of the applied magnetic field are observed. The experimental results are in qualitative agreement with the micromagnetic simulations. These findings may find application in the design of magnetically controlled tunable microwave filters. Abstract : The nanofabrication of large area artificial spin ice and anti‐spin ice structures by using deep ultraviolet lithography at 193 nm exposure wavelength is reported. The method allows to arrange the magnetic elements in three different lattice configurations. It is demonstrated that the static and dynamic behaviors of these structures are highly tunable. The results are validated using micromagnetic simulations.